Review of Indonesia-Palestine Solidarity Relations: Why is it so Strong? - Kurniadi, Agil (Terekam Jejak Publisher, 2024)
This research discussed reevaluation of the relationship between Indonesia and Palestine. Throughout history in relation of two countries, the relationship has strong solidarity among between the two parties. The author is going to analyze why the solidarity among two nations was very consistent in the long term. In research, the author discovered several important factors: historical, ideological, and humanitarian. This research used qualitative method by references study approach. By reconsideration toward of two states relations, this research pointed new reflection on the relationship between Indonesia and Palestine in the future.